Zero-profile implant (Zero-p) versus plate cage benezech implant (PCB) in the treatment of single-level cervical spondylotic myelopathy - Wang, ZhiDong (BMC Musculoskelet Disord, 2015)
BACKGROUND: Anterior cervical discectomy and fusion is the golden standard for anterior surgery treating elderly cervical degenerative disease, but the previous implant has some problems such as looseness, translocation, sinking and dysphagia, So Zero-p implant and PCB implant have been developed to decrease the complications. METHODS: The clinical data of 57 patients with single level cervical spondylotic myelopathy were retrospectively analyzed. 27 patients adopting Zero-p interbody fusion cage as implant (Zero-p group) and 30 patients adopting integrated plate cage benezech (PCB) as implant (PCB group) from January 2010 to October 2012. Observe whether are differences between the two groups of patients on operation time, intraoperatve blood loss,Japanese Orthopaedic Association (JOA) scores before and after operation, intervertebral height, cervical physiological curvature, fusion rate, Postoperative dysphagia rate and complications. RESULTS: Zero-p group’s operation time is 98.2 + 15.2 min and its intraoperatve blood loss is 88.2 + 12.9 ml, both of which are lower than those of PCB group (109.8 + 16.9 min,95.2 + 11.6 ml ), so their differences are statistically significant (P < 0.05). The two groups’ JOA scores 3 months after operation and in the last follow-up are significantly higher than those before operation, so the differences are statistically significant (P < 0.05). Coob angle 3 months after operation and in the last follow-up improves obviously compared with before operation, so the difference is statistically significant (P < 0.05). The two groups’ operation segments intervertebral height 3 months after operation and in the last follow-up improves obviously compared with before operation, so the difference is statistically significant (P < 0.05) Zero-p group has one patient with dysphagia after operation and PCB group has four patients with dysphagia after operation, so there is no statistical differences between the two groups on dysphagia rate (P > 0.05, P = 0.415). PCB group has two patients with screws backing out and two patients with hoarseness after operation, the two groups’ operation segments all saw bony union in the last follow-up. Zero-p group postoperative complications are lower than PCB group (P < 0.05, P = 0.044). CONCLUSIONS: Zero-profile implant and PCB implant both achieved good clinical effects on the treatment of cervical spondylotic myelopathy, the two groups both saw bony union in operation segments, but Zero-profile implant has the advantages of easy operation, short operation time, less intraoperatve blood loss and less complications.